Autophagy and cancer – insights from mouse models. (3rd October 2017) - Mainz, Laura; Rosenfeldt, Mathias T.
Abstract : (Macro‐)autophagy is an evolutionary conserved 'self‐digestion program' that serves to maintain cellular metabolism and is implicated in many pathological processes such as cancer. In recent years, an increasing number of studies in murine cancer models have provided a plethora of sometimes conflicting results about the role of autophagy in cancer biology. This review summarizes these studies and raises awareness that there are situations in which autophagy blockage might indeed reduce tumor growth, but that sometimes the exact opposite is the case. It is therefore vital to mimic patient conditions in preclinical mouse experiments as thoroughly as possible before commencing clinical trials. Abstract : This review summarizes how autophagy blockage impacts on tumor biology in murine cancer models. It will sensitize the reader about mouse model categories and the conclusions that can be drawn from the multitude of in vivo studies about autophagy and cancer.